Functionalization of α-zirconium phosphate by polyphosphazene and its effect on the flame retardance of an intumescent flame retardant polypropylene system. Issue 81 (16th August 2016) - Xu, Lingfeng; Lei, Caihong; Xu, Ruijie; Zhang, Xiaoqing; Zhang, Feng
Abstract : α-ZrP was combined with polyphosphazene and formed a core–shell structure, which has a significant synergistic flame retardant performance in polypropylene. Abstract : A kind of core–shell flame retardant, functionalized α-zirconium phosphate (FZ) was prepared by wrapping α-zirconium phosphate (α-ZrP) with a kind of polyphosphazene to shield the solid acid sites on the surface of α-ZrP. The synergistic effect between polyphosphazene and α-ZrP was studied. The effects of FZ on the thermal properties and flame retardance of intumescent flame retardant polypropylene (IFR/PP) composites were investigated. It was found that the presence of FZ improved the thermal stability of the matrix and increased the amount of char yield at 800 °C significantly. For IFR/PP composites, the LOI of the composites was only 26.4% and the V-1 rating was obtained by UL-94 vertical testing. With an increase of FZ content to 3 wt%, the composites could achieve a LOI value of 32.8% and a UL-94 V-0 rating, whereas, without a coating layer of polyphosphazene, the LOI of the composite decreased to 27.5% and a V-1 rating was obtained. A synergistic effect between FZ and IFR was found. During the primary stage of combustion, the functional layer was decomposed and could quench free radicals from PP chain scission, and in the later stage, could also promote char formation due to the presence of solid acid sites on the surface of uncovered α-ZrP, thus a continuous and compact intumescent char was produced on the substrate.